Level of Knowledge and Attitude of Street Children about HIV/AIDS Incidence in Mataram City - Siti Mardiyah WD; Ultimate Chess Esty; Aulia Amin (Universitas Muhammadiyah Semarang, 2023)
The number of HIV infections in NTB Province from the first time it was found up to March 2017 was 1,279, while the number of AIDS infections from 1987 to March 2017 was 704 people. The most risk factors for transmission are through heterosexuals (68%), IDUs (11%), followed by homosexuals (4%) and perinatal transmission (3%). Poor or wrong understanding of sexual problems puts teens at risk of unprotected sexual relations, such as changing partners, using drugs and not using condoms. Street children are one of the vulnerable groups infected with HIV. Describe the Level of Knowledge and Attitudes of Street Children about the Incidence of HIV / AIDS in the City of Mataram. Descriptive research method using a cross-sectional study design. The research location is in the city of Mataram. The population in this study were 30 street children in the city of Mataran. The sampling technique in this study was consecutive sampling. Analysis using univariate analysis. Results: the level of knowledge of street children about the incidence of HIV / AIDS in the city of Mataram which is the most knowledgeable is 22 people (73.3%) and in line with the good attitude that is 27 people (90%).